Supporting Ethical Decisions in Wearable Technology with Deontic Logic: A Brief Introduction - Zafeirakopoulos, Dimitrios; Almpani, Sofia; Stefaneas, Petros (Electronic Communications of the EASST, 2022)
The purpose of this article is to give a small introduction of deontic logic in the world of wearable technology and show how we hope deontic logic could be used to address some of the issues concerning both the users and the developers of wearable technology by providing ethical frameworks expressed in formal logic. We begin by presenting a short overview of what we view as major issues concerning wearable technology. After a brief introduction to deontic logic, we show how deontic logic might be helpful towards addressing the concerns we have presented. Finally, we give a small, introductory application of deontic logic, showing exactly how it can be used to address one of these issues regarding wearable technology with a concrete example.